Summary of osteomucosal healing patterns. - Sol Kim (331410) (2025)
Wound closure occurs progressively in a time-dependent manner (red). The presence of osteoclasts (purple) and the formation of collagen (green) fibers occur as early as day 2. Newly forming woven bone (pink) starts forming at day 5 and increases rapidly at day 7.